2010
DOI: 10.1111/j.1749-0774.2010.00096.x
|View full text |Cite
|
Sign up to set email alerts
|

Value of human amniotic epithelial cells in tissue engineering for cornea

Abstract: Human amniotic epithelial cells (hAECs) are potentially one of the key players in tissue engineering due to their easy availability. The aim of the present study was to develop an optimal isolation and transportation technique, as well as to determine the immunophenotype and epithelial gene expression of hAECs. Amnion was mechanically peeled off from the chorion and digested with trypsin-ethylenediaminetetraacetic acid. The isolated hAECs were cultured in medium containing 10 ng/mL epidermal growth factor unti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
28
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 31 publications
5
28
0
Order By: Relevance
“…This is similar with previous studies on other epithelial cells such as epidermal keratinocytes (11,12,16) and oropharyngeal keratinocytes (14). In some other studies, different concentrations of EGF were added to HAECs culture medium (2,3,7,8) to support the cells' proliferation. However, other growth supplements were also added to their culture medium such as fetal bovine serum, L-glutamine, PDGF, FGF, insulin and hydrocortisone (2,3,7,8).…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…This is similar with previous studies on other epithelial cells such as epidermal keratinocytes (11,12,16) and oropharyngeal keratinocytes (14). In some other studies, different concentrations of EGF were added to HAECs culture medium (2,3,7,8) to support the cells' proliferation. However, other growth supplements were also added to their culture medium such as fetal bovine serum, L-glutamine, PDGF, FGF, insulin and hydrocortisone (2,3,7,8).…”
Section: Discussionmentioning
confidence: 66%
“…In some other studies, different concentrations of EGF were added to HAECs culture medium (2,3,7,8) to support the cells' proliferation. However, other growth supplements were also added to their culture medium such as fetal bovine serum, L-glutamine, PDGF, FGF, insulin and hydrocortisone (2,3,7,8). Based on this study, it was found that 10 ng/ml EGF added to the culture medium could be the minimal concentration of EGF required to significantly increase the total number of cultured cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore there are negative for KRT3=12, but were better for amniotic membrane and thermo responsive substrate than modified porous scaffold ( Figure 5). In recent years, many carriers have been used to culture limbal stem cells; however, the majority of previous studies have used amniotic membrane as a choice of carrier due to its low-cost procurement, easy availability, promote epithelialization, and reduced inflammation and scarring [30,31]. Nonetheless, due to its biologic origin, amniotic membrane carries inherent risks such as disease transmission and infection that cannot be totally avoided [32].…”
Section: Immunocytochemistrymentioning
confidence: 98%
“…HAM is currently the most commonly used substrate for LESCs cultivation and transplantation. [38][39][40][41] Although the results are quite promising, amniotic membrane does have some shortcomings. One of the major issues is ensuring the biosafety of HAM in disease transmission, e.g., HIV, hepatitis B and C as well as from bacteria and fungus which will grow readily on HAM.…”
Section: Recent Advancesmentioning
confidence: 99%